Wastewater Analysis of X Slaughterhouse in Pontianak City - Heraini, Dela; Rohayeti, Yeti (Politeknik Negeri Jember, 2024)
Livestock waste results from livestock activities in the form of solid, and liquid waste. Generally, waste is not utilized, causing environmental pollution. The Slaughterhouse is a place where cattle slaughtering activities are carried out usually leaving behind various wastes in the form of cow offal, cow blood, cow urine and feces, also skin, if it is not handled properly it will cause an unhealthy environment and can cause the meat to be contaminated by microbes that exist around the slaughterhouse environment. This research aims to analyze wastewater from the Pontianak City Slaughterhouse. The research parameters consist of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), pH, ammonia, fat, and oil tests. Data analysis uses quantitative descriptive analysis. The results showed that the wastewater produced from the livestock slaughtering process at slaughterhouse X Pontianak City was highly above the standard threshold of wastewater quality standards for BOD, COD, TSS, ammonia, and fatty oil, but the pH was within the standard. It can be concluded that the practice of processing wastewater produced by slaughterhouse X in Pontianak City was not optimal, the quality of wastewater was above the standard value of wastewater quality for slaughterhouse activities.